Dante's prayerful pilgrimage - Vettori, Alessandro, author.
1 online resource.
Keywords: In Dante’s Prayerful Pilgrimage Alessandro Vettori provides a comprehensive analysis of prayer in Dante’s Commedia . The underlying thesis considers prayer a metaphorical pilgrimage toward a sacred location and connects it with the pilgrim’s ascent to the vision of the Trinity. Prayer is movement in Purgatorio and also in Paradiso, while eternal stasis is the penalty of blasphemous souls in Inferno . In the fictional rendition of the poem, the pilgrim’s itinerary becomes a specular reflection of Dante’s own exilic experience. Prayer’s human-divine interaction affords the poet the necessary escape from the overwhelming sense of failure in politics and love. Whether it is petitional, liturgical, thankful, praiseful, or contemplative, prayer expresses the supplicant’s wish to transform reality and attain a superior spiritual status.